Determination of Kinetic Parameters and Formation Constants of In(III)-3-Hydroxy-3-o-Tolyl-1-(p-Carboxy-phenyl) Triazene (HOTCPT) and In(III)-3-Hydroxy-3-Ethyl-1-(p-Carboxyphenyl) Triazene (HECPT) Complexes&
The interaction of In3+ with hydroxy triazene has been studied at dropping mercury electrode at a constant ionic strength. The reductions were diffusion controlled but quasi-reversible. The Er1/2 have been obtained by Gelling's method and the formation constants of the complexes formed have been evaluated by Deford and Hume's method. In(iii) forms four complex species with 3-hydroxy-3-o-tolyl-1-(p-carboxyphenyl) triazene (HOTCPT) and 3-hydroxy- 3-ethyl-1-(p-carboxyphenyl) triazene